Common Spaces in Cantiga by José Manuel Arango - Henao, Simón (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper reviews the tension between presencia común [common spaces] and amazementwhich shape José Manuel Arango’s poetry. On one hand, this tension embodies the poet’s subjective experience and on the other hand reality as the essential feature of his poetry. As one of his interpreter states that Cantiga (1987) is a rewritten work of two previous poems, this paper suggests a critical review from the context of his writing to the theoretical framework regarding common spaces. The result of this research shows that Cantiga determines a poet inserted in the world plentily observed by him and then names it. From this point of view, this José Manuel Arango’s work expresses the   division between the poetic subject and the world.